Initial Experience of Corneal Collagen Cross Linking in Progressive Keratoconus - Muhammad Ahsan Sulaiman, Munira Shakir, Faiza Rameez , Shakir Zafar (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the outcome of Corneal Collagen Cross-linking (CCXL) in patients with progressive Keratoconus in terms of satisfaction. Study Design: Descriptive case series. Place and Duration of Study: This study was conducted at Liaquat National Hospital, Karachi, Pakistan. It documents a process that is spread on one year. Material and Methods: This prospective study is comprised of 34 patients who had bilateral Corneal Cross linking (CXL) treatment for progressive Keratoconus. Analysis was performed in terms of amount of corneal flattening (observed through topography), effect on vision (observed through Snellen’s Chart) and satisfaction of patient (assessed by filling of proforma 6 months post-operatively). Results:. Findings of 31 cases were analyzed as 3 cases missed the follow-up. Mean age was 23.2 ± 5.5 years. 61.3% of the cases were males while 38.7% were females with respective frequency of 19 and 12. Mean post-operative BCVA on Snellen’s Chart improved on average by more than one line. Post-operative mean of change in steepest K reading was 1.29 ± 0.52D. 16.13% of the cases were happy after treatment, while 64.52% were satisfied. However, 19.35% of the cases were unhappy. Conclusion: This study shows that CXL retards progression and generally brings satisfaction among the participants. Keywords: Corneal Collagen Cross linking, Keratoconus, Corneal Topography.